Implementasi SIMP dalam Meningkatkan Efektivitas Administrasi Sekolah - Usmila Usmila; Mohammad Faizal; Muhammad Ali Imron; Eka Pratiwi; M. Ubaidillah; Yeni Tri Nur Rahmawati (CV. Lentera Literasi Indonesia, 2026)
Technological advancements require educational institutions to transition from manual to digital management to increase efficiency. This study aims to analyze the implementation of the Educational Management Information System (EMIS) in improving the effectiveness of school administration. The research method used is descriptive qualitative with a case study approach in a school environment. Data collection was conducted through observation, documentation, and interviews with administrative staff, the school principal, and teachers. The results show that the integration of EMIS significantly accelerates the processing of student data, financial management, and the compilation of academic reports. The main obstacles encountered include limited digital infrastructure and variations in the technical readiness of human resources. However, with structured training, EMIS is proven to cut administrative workload time by more than 40% and reduce the risk of data entry errors. In conclusion, EMIS is a crucial instrument in creating transparent, accurate, and accountable school governance.